2005
DOI: 10.1039/b415229h
|View full text |Cite
|
Sign up to set email alerts
|

Adenophostin A and analogues modified at the adenine moiety: synthesis, conformational analysis and biological activity

Abstract: The synthesis of adenophostin A (2) and two analogues [etheno adenophostin (4) and 8-bromo adenophostin (5)] modified at the adenine moiety, is reported. A combination of NMR analysis and molecular modelling was used to compare their structures in solution and determined that they all adopt very similar conformations. The analogues were tested for their ability to mobilise Ca(2+) from DT40 cells expressing recombinant Type 1 rat Ins(1,4,5)P(3)R which reveals etheno adenophostin as a high affinity fluorescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
(43 reference statements)
0
21
0
Order By: Relevance
“…AdA, a fungal glyconucleotide metabolite (448), and its many analogs (1,23,51,102,290,388,397,398,420,444,465) were discovered as agonists of the InsP 3 R. Although their molecular structures are significantly different from those of InsP 3 and its analogs (198), they activate the channel by interacting with the InsP 3 binding site (157). AdA binds InsP 3 R with substantially higher affinity and is significantly more potent in stimulating InsP 3 Rmediated Ca 2ϩ release than its natural agonist InsP 3 .…”
Section: H Activation Of Insp 3 R Channel By Adenophostin and Its Anmentioning
confidence: 99%
See 1 more Smart Citation
“…AdA, a fungal glyconucleotide metabolite (448), and its many analogs (1,23,51,102,290,388,397,398,420,444,465) were discovered as agonists of the InsP 3 R. Although their molecular structures are significantly different from those of InsP 3 and its analogs (198), they activate the channel by interacting with the InsP 3 binding site (157). AdA binds InsP 3 R with substantially higher affinity and is significantly more potent in stimulating InsP 3 Rmediated Ca 2ϩ release than its natural agonist InsP 3 .…”
Section: H Activation Of Insp 3 R Channel By Adenophostin and Its Anmentioning
confidence: 99%
“…Thus AdA has been applied as a metabolically stable InsP 3 substitute in studies of the InsP 3 R and its regulation (5,157,179,203,223,316,445,487), Ca 2ϩ release mediated by InsP 3 R (37, 292) and Ca 2ϩ entry due to depletion of intracellular Ca 2ϩ stores (60,107,160,172,193,265). Investigations into the InsP 3 R binding affinity and biological activity of AdA and its analogs have also provided insights into the structural determinants for ligand interactions with the InsP 3 binding site of the channel (51,93,332).…”
Section: H Activation Of Insp 3 R Channel By Adenophostin and Its Anmentioning
confidence: 99%
“…[2,3] A search for InsP 3 R agonists revealed the highly potent naturally occurring adenophostins, [4] for which an extensive set of synthetic analogues and corresponding data of structure-activity relationships has been accumulated. [5] We sought to prepare stabilized, cell-permeant, highaffinity small molecules that could act as InsA C H T U N G T R E N N U N G (1,4,5)P 3 agonists or antagonists. To this end, we turned to the cyclopentanebased InsP 3 R ligands, in particular trisphosphate 2 ( Figure 1), which had only a 2-4-fold lower affinity than InsA C H T U N G T R E N N U N G (1,4,5)P 3 .…”
mentioning
confidence: 99%
“…1B). Despite considerable effort, fuelled by synthesis of many adenophostin A-related analogs (Borissow et al, 2005;Mochizuki et al, 2006;Sureshan et al, 2008), the structural basis of the high-affinity binding of adenophostin A to IP 3 R is unresolved. We have suggested that a cation-interaction between the adenine moiety of adenophostin A and Arg-504 within the IBC may contribute to this high-affinity binding (Sureshan et al, 2009).…”
mentioning
confidence: 99%